Analysis of Ferritin Levels, TIBC and Fe Serum In Central Obesity And Non Central Obesity - Nuril Sofiantin; Liong Boy Kurniawan; Mansyur Arif (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Ferritin is an inflammatory marker in obesity, TIBC, Fe, and transferrin saturation by examining iron status. Anthropometric parameters of waist circumference are related to visceral fat. This study analyzed the levels of ferritin, TIBC, Fe, and transfer saturation in central and non-central obesity. The observational study (cross-sectional) used 75 subjects for 4 months. Ferritin using ECLIA, TIBC and Fe using immunoturbidimetric and colorimetric methods, transferrin saturation using the comparison method of Fe and TIBC values ​​in percent units. This study showed significant results on TIBC levels, while levels of ferritin, Fe, and transferrin saturation were not significant. The Spearman correlation test showed significant results between ferritin and waist circumference levels while TIBC, Fe, and transferrin saturation were not significant. In conclusion, there are significant differences in TIBC while ferritin, Fe, and transferrin saturation do not have significant differences between central and non-central obesity